On an approximate method for calculating filters based on acoustic surface waves - Zenon CEROWSKI; Aleksander OPILSKI; Tadeusz PUSTELNY; Marian URBAŃCZYK (Archives of Acoustics)
The work describes an electric filter consisting of interdigital transducers deposited on piezoelectric substrate. A method has been presented for computing the transducer parameters with an assumed amplitude-frequency cha¬racteristic. The filters produced on the basis of calculated transducer parameters were tested and the results are given in this paper.